Evaluation of Educational Standards at The Level of Early Childhood Education - Lestari, Sevi; Muchtarom, Muchtarom; Gustami, Belina Anggia; Gumelar, Nur Devi Yusiawati (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Increasing the number of ECCE institutions must pay attention to the quality of management standards so that they become quality institutions. The purpose of this study is to know and describe education management standards based on Permendikbud number 137 of 2014 concerning ECCE standards and to determine obstacles in the implementation of education standards. This research uses a qualitative approach. While the method used is a descriptive method of evaluation analysis of the Implementation of Early Childhood Education Standards. Location of research site TK Mekar Arum Bandung. Data collection techniques using observation, interviews, questionnaires, documentaries The results showed that Mekar Arum Kindergarten has conducted education in accordance with the criteria of ECCE education standards even though there is one standard that allegedly has not met the standards, namely assessment standards, while 7 other standards have met the standards in accordance with Constitution Number 137 of 2014. Obstacles in the implementation of education standards have been sought solutions together by increasing budget allocation, carrying out training and development of educators and increasing public awareness